Multi-objective sustainability optimization of CCHP systems considering the discreteness of equipment capabilities - Ren, Xusheng; Ding, Shimin; Dong, Lichun; Qin, Lixiao (Journal of Environmental Engineering and Landscape Management, 2021)
The value of waste heat had led to an extensive study on Combined Cooling, Heating and Power (CCHP) system in recent decades, but the following three research gaps still need to be tackled to achieve a better economic and environmental performance. Firstly, the complete discreteness of equipment capabilities had not been considered. It means that multiple units with different capacities cannot be selected for a type of equipment. Then, the ambiguity and subjectivity existing in decision-makers/stakeholders’ judgments on the importance of objectives are usually ignored. Finally, an easily understood and comprehensive environmental indicator based on life cycle perspective for system optimization had not been established. Thus, the aim of this study is to establish a mathematical framework to help the stakeholders select the optimal configurations, capacities, and operation conditions of CCHP system while narrowing the above three research gaps to avoid the sub-optimal solutions. Subsequently, a hypothetical case was used to verify the validity of the proposed model, along with analysis of system performance. The results indicate that the CCHP system is superior to the conventional systems, and the proposed mathematical model in this paper can improve the performance of CCHP system in terms of economy, environment, and energy.